A Tablet-Based Technology for Objective Exercise Monitoring in Vestibular Rehabilitation: Mixed Methods Study - Brooke N Klatt; Pedram Hovareshti; Lisa S Holt; Pamela M Dunlap; Chad Zalkin; Devendra Tolani; Susan L Whitney (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundA low-cost home exercise system called VestAid has been developed to assist participants during vestibulo-ocular reflex gaze stabilization exercises outside of clinic visits. The system includes a tablet-based app for the participant and a web-based portal for the physical therapist that provides data to make judgments about exercise accuracy and performance. ObjectiveThe purpose of this study was to assess the feasibility and acceptability of VestAid in a pilot study of 10 participants (mean age 45 [SD 19] years; 6 women) with various vestibular diagnoses. MethodsAll participants completed twelve 30-second horizontal vestibulo-ocular reflex exercises in a seated position (6 “easy” and 6 “hard” exercises). The exercises differed by variations in the background color, pattern, and movement. One of the exercises was repeated to assess the test-retest reliability of the measure of gaze stability accuracy and head motion compliance during the exercise. Participants rated the difficulty of the exercises (0‐10 where 0=easy, 10=difficult) and completed usability surveys. ResultsParticipants completed the VestAid session without adverse events. The responses from the usability survey demonstrate the acceptability of VestAid. The mean rating of the “easy” exercises was 2.7/10 (SD 1.9). The mean rating for the “difficult” exercises across participants was 4.8/10 (SD 2.1). ConclusionsThe consistency of the mean ratings of the participants with the exercise classifications (“easy” and “difficult”) suggests that VestAid has clinical utility.